ANALISIS PEMBERITAAN POLEMIK SUMBANGAN RP 2 TRILIUN AKIDI TIO (ANALISIS FRAMING PADA DETIK.COM DAN TIRTO.ID) - Aditya Muhaimin Andika; Adi Nugroho; Primada Qurrota Ayun (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
The media has certain characteristics in framing news, especially news that is trending or in the public spotlight. These differences in characteristics are caused by several factors, including; (1) the interests of media owners, (2) the demands of interests as an economic institution, (3) the ideological differences of each media, and (4) the subjectivity of journalists in presenting news. In this study, the selected research object is one of the news that is currently in the spotlight, namely the polemic case of a donation of Rp 2 trillion in grant funds for the prevention of the Covid-19 pandemic in the South Sumatra area, which was carried out by Akidi Tio's son, Heriyanty. This report was chosen because the researcher assumed that there were differences in the framing of the news between Detik.com and Tirto.id regarding the case. Based on these problems, the purpose of this research is to identify, analyze, and describe the news framing used in reporting on the polemic of Akidi Tio's Rp 2 trillion contribution to Detik.com and Tirto.id. The paradigm used in this research is constructivism paradigm. This study uses a qualitative methodology with framing analysis as an analytical tool. The framing analysis model used in this study is the framing model of Robert N Entman. The theory used to complete this research is the theory of mass media social construction. Referring to the aims and objectives of the study, the results of the study are as follows: 1) Detik.com often makes news headlines that lead readers' opinions, so they tend to corner one party on the news. Meanwhile, Tirto.id is more neutral in making news headlines. 2) Detik.com and Tirto.id have different views in reporting on the causes of problems in a case. Detik.com in this case is more diverse in raising opinions from various parties, while Tirto.id only raises opinions from parties related to the case, especially from the police. 3) Overall, there are differences in the framing of the news between Detik.com and Tirto.id, namely Detik.com tends to blame Akidi Tio's son, Heriyanty, who is considered the source of the problem in the case, while Tirto.id tends to corner the police (Kapolda Sumsel) because deemed negligent of their duties and responsibilities. 4) In reporting on the polemic of the Rp 2 trillion donation case by Akidi Tio, both Detik.com and Tirto.id should report in a balanced manner, neither taking sides nor cornering one party. Thus, the public can consume accurate news from these online media.